ANALISIS HUKUM PERAN PENGAWASAN SYAHBANDAR DALAM PENGIRIMAN BARANG DI PELABUHAN NUSANTARA PAREPARE - Sadriyah Mansur, Nurhaedah Hasan, Irma Reisasari (FAKULTAS HUKUM UM PAREPARE, 2023)
Delivery of goods is very necessary to meet socio-economic needs, therefore supervision is needed by the port management unit to oversee every shipment of goods that occurs so that illegal shipments of goods do not occur. The research with the title